Dynamic Performance of Timber Diaphragms in an Unreinforced Masonry Building. - Wilson, Aaron; Abdul Razak, Abdul Karim; Oyarzo-Zera, Claudio; Omenzetter, Piotr; Ingham, Jason M. (2008)
The flexibility of timber diaphragms in unreinforced masonry buildings has been reported to have a significant effect on the seismic performance of the complete structure. In New Zealand, there currently exists a need to improve the knowledge and expertise associated with the performance of timber diaphragms to assist the seismic assessment of unreinforced masonry buildings and design of seismic retrofit solutions. To address this issue, a series of modal tests were conducted on the third floor timber diaphragm of the Nathan Building located in Auckland’s Britomart Precinct, which is a building typical of New Zealand historic unreinforced masonry construction. Preliminary analysis indicates that the fundamental horizontal natural frequency occurs at 20.5 Hz which reasonably matched the finite element model, which predicted a frequency of 18.49 Hz. Further testing, system identification and finite element updating is required to determine accurate dynamic diaphragm properties. An investigation of typical New Zealand diaphragm details was also conducted to aid future testing and finite element modelling.